Catalyst ink for fuel battery electrode
The catalyst ink with a specific solvent system improves ionomer adsorption on carriers, addressing electrode cracking and enhancing fuel cell durability by stabilizing the electrolyte membrane.
Patent Information
- Application Number
- JP2023093959
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2024-12-19
AI Technical Summary
Ionomers with high oxygen permeability have low adsorption to carriers, leading to electrode cracking and deteriorating fuel cell durability due to carrier aggregation.
A catalyst ink using a polar solvent with a Rohrschneider polarity parameter of 5.1 or more, or a mixed solvent with a 70% blending ratio, to improve ionomer adsorption on carriers, suppressing electrode cracking.
The catalyst ink effectively suppresses electrode cracking and enhances fuel cell durability by improving ionomer adsorption, thereby stabilizing the electrolyte membrane.
Smart Images

Figure 2024175880000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to catalyst inks for fuel cell electrodes. [Background technology]
[0002] Various studies have been conducted on fuel cells (FC). Patent Document 1 describes a fuel cell that includes catalyst-supported particles, which are particles that support a catalyst, an ionomer having proton conductivity, and a dispersion solvent for dispersing the catalyst-supported particles and the ionomer, and that has an adsorption amount of the ionomer per unit specific surface area of the catalyst-supported particles of 0.1 (mg / m 2 ) and thus, a catalyst ink used for manufacturing fuel cell electrodes is disclosed, which suppresses cracks from occurring in the fuel cell electrodes. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2013-030287 A Summary of the Invention [Problem to be solved by the invention]
[0004] It may be possible to use an ionomer with high oxygen permeability instead of an ionomer with proton conductivity. However, since an ionomer with high oxygen permeability is less adsorbed to a carrier such as carbon in the catalyst ink and the carrier surface is exposed, if an ionomer with high oxygen permeability is used, cracks will occur in the electrodes, accelerating the deterioration of the electrolyte membrane and reducing the durability of the fuel cell.
[0005] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide a catalyst ink for fuel cell electrodes that can reduce the affinity between a solvent and an ionomer, improve the amount of ionomer adsorbed onto a carrier, and suppress cracking of the electrode. [Means for solving the problem]
[0006] The present disclosure provides a catalyst ink for a fuel cell electrode having the following characteristics: A catalyst ink for a fuel cell electrode, comprising: A catalyst particle including a support and a catalytic metal supported on the support; An ionomer having high oxygen permeability and proton conductivity; A dispersion solvent for dispersing the catalyst particles and the ionomer, Catalyst ink, characterized in that the dispersion solvent is a polar solvent having a Rohrschneider polarity parameter of 5.1 or more, or a mixed solvent containing the polar solvent in a blending ratio of 70% or more.
[0007] In the present disclosure, the ionomer may have a five-membered ring in its unit structure.
[0008] In the present disclosure, the polar solvent may be at least one selected from the group consisting of water, dimethyl sulfoxide, ethylene glycol, acetonitrile, and acetone.
[0009] In the present disclosure, the polar solvent may be at least one of water and ethylene glycol.
[0010] In the present disclosure, the specific surface area of the carrier is 40 to 1600 m 2 / g. Effect of the Invention
[0011] The present disclosure can provide a catalyst ink for fuel cell electrodes that can suppress cracking of the electrodes. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is an image showing the criteria for judging whether a catalyst layer has cracks, with the image on the left being rated as "x," the image in the middle being rated as "△," and the image on the right being rated as "o." DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, embodiments of the present disclosure will be described. Note that matters other than those specifically mentioned in this specification and necessary for implementing the present disclosure (for example, the general configuration and manufacturing process of a catalyst ink for fuel cell electrodes that does not characterize the present disclosure) can be understood as design matters of a person skilled in the art based on the prior art in the field. The present disclosure can be implemented based on the contents disclosed in this specification and the technical common sense in the field. In this specification, the use of "to" indicating a numerical range means that the numerical values before and after it are included as the lower limit and upper limit. Furthermore, any combination of upper and lower limits in a numerical range can be used.
[0014] The present disclosure provides a catalyst ink for a fuel cell electrode having the following characteristics: A catalyst ink for a fuel cell electrode, comprising: A catalyst particle including a support and a catalytic metal supported on the support; An ionomer having high oxygen permeability and proton conductivity; A dispersion solvent for dispersing the catalyst particles and the ionomer, Catalyst ink, characterized in that the dispersion solvent is a polar solvent having a Rohrschneider polarity parameter of 5.1 or more, or a mixed solvent containing the polar solvent in a blending ratio of 70% or more.
[0015] If the ionomer having proton conductivity used in Patent Document 1 is changed to an ionomer having high oxygen permeability, cracks will occur in the electrodes. The cracks in the electrodes accelerate the deterioration of the electrolyte membrane and deteriorate the durability of the fuel cell. The carriers aggregate due to a decrease in the amount of ionomer adsorbed to the carrier such as carbon. When ionomer is adsorbed to the carrier surface, carrier aggregation is suppressed by electrostatic repulsion and steric hindrance effects, but since the amount of ionomer with high oxygen permeability adsorbed to the carrier is significantly small, the carrier surface is exposed and carriers tend to aggregate. In the present disclosure, the dispersion solvent for the catalyst ink is a polar solvent with a Rohrschneider polarity parameter of 5.1 or more, or a mixed solvent containing the polar solvent at a blending ratio of 70% or more. This reduces the affinity between the solvent and the ionomer, thereby improving the amount of ionomer adsorbed to the carrier, and suppressing cracks that occur in electrodes using an ionomer with high oxygen permeability. In the present disclosure, the carrier to which the ionomer is adsorbed may be either a carrier alone or a carrier carrying a catalytic metal (a catalytic metal-supported carrier).
[0016] The catalyst ink of the present disclosure includes catalyst particles, an ionomer, and a dispersion solvent.
[0017] The catalyst particles (catalytic metal-supporting carrier) include a carrier and a catalytic metal supported on the carrier. Examples of the catalytic metal include platinum, ruthenium, iridium, rhodium, palladium, osnium, tungsten, lead, iron, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, and yttrium, and two or more of these metals may be used. The metal may also be an oxide, nitride, sulfide, phosphide, or the like. The catalytic metal may be platinum, platinum alloys, and the like. Examples of metals other than platinum contained in the platinum alloy include ruthenium, iridium, rhodium, palladium, osmium, tungsten, lead, iron, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, and yttrium, and two or more of these metals may be contained. The catalyst metal may be platinum, a platinum-cobalt alloy, a platinum-nickel alloy, and the like. The catalytic metal may be catalytic metal particles that are particulate in shape. The particle size of the catalytic metal particles is not particularly limited, but may be from 1 nm to 100 nm. The catalytic metal is supported on a support.
[0018] In this disclosure, the particle size of catalyst particles refers to the volume-based median diameter (D50) value measured by laser diffraction / scattering particle size distribution measurement. In addition, in this disclosure, the median diameter (D50) refers to the diameter (volume average diameter) at which the cumulative volume of particles is half (50%) of the total volume when the particles are arranged in order of decreasing particle size.
[0019] The carrier is a carrier particle that is particulate in shape. The carrier may be either a primary particle or a secondary particle. The support supports a catalytic metal. The method for supporting the catalytic metal on the carrier is not particularly limited, and any conventionally known method can be appropriately adopted. The support may be acetylene black, ketjen black, channel black, roller black, disc black, oil furnace black, gas furnace black, lamp black, thermal black, activated carbon, graphite, glassy carbon, graphene, carbon fiber, carbon nanotubes, carbon nitride, carbon sulfide, and carbon phosphide, or a mixture containing at least two of these.
[0020] The specific surface area of the support is 40 to 1600 m 2 / g. In this disclosure, the specific surface area is the BET specific surface area measured by the BET method.
[0021] The particle size of the carrier may be 30 to 1000 nm. In the carrier of the present disclosure, the equivalent circle diameters of 100 to 1000 particles are calculated as the particle diameter using an electron microscope, and the average particle diameter of these may be regarded as the particle diameter of the particles. The particle diameter of the carrier particles can be measured using 3D-TEM or the like.
[0022] Ionomers have high oxygen permeability and proton conductivity. The amount of ionomer contained in the catalyst ink may be equal to or greater than 1% by weight and less than 10% by weight.
[0023] The number average molecular weight Mn of the ionomer is not particularly limited, but may be 5,000 to 100,000 or 20,000 to 50,000 from the viewpoints of ensuring chemical stability and catalyst layer strength.
[0024] The oxygen permeability of the ionomer at a temperature of 80°C and a relative humidity of 30% is 2.0 x 10 -14 mol / m / sec / Pa or more. If the oxygen permeability is equal to or greater than the lower limit, the ionomer has high oxygen permeability. The upper limit of the oxygen permeability is not particularly limited, but from the viewpoint of being prone to drying due to excessive gas permeability, it is preferable that the upper limit be 5.0×10 -14 It may be mol / m / sec / Pa or less. The oxygen permeability can be measured, for example, by casting the electrolyte resin into a thin film having a thickness of about 0.2 mm and subjecting it to linear sweep voltammetry (LSV) using a micro Pt electrode.
[0025] The ionomer may have a proton-conducting group such as a sulfonic acid group. From the viewpoint of ion conductivity in the entire catalyst layer, the ionomer may have an equivalent weight (EW; unit "g / mol") of the proton-conducting group (e.g., sulfonic acid group) of 1500 g / mol or less, 1200 g / mol or less, or 1000 g / mol or less. Here, the equivalent weight of the proton-conducting group means the dry weight of the proton-conducting group relative to the total mass of the ionomer. In addition, considering the mobility of water from the viewpoint of hydrophilicity in the entire catalyst layer, the lower limit of the EW of the ionomer may be 500 g / mol or more, 600 g / mol or more, or 700 g / mol or more. The dry weight of the proton-conducting group can be measured by a known method such as back titration using an aqueous NaOH solution.
[0026] The ionomer having high oxygen permeability may have a five-membered ring in the unit structure. An example of the ionomer having high oxygen permeability is an ionomer having a unit structure represented by the following formula (1).
[0027] [ka]
[0028] (In formula (1), R 1 ~R 4 each independently represents F or a perfluoroalkyl group having 1 to 10 carbon atoms; A 1 None, F, SO3H, or SO2-NH-SO2-A 2 A 2 is a perfluoroalkyl group having 1 to 10 carbon atoms, (CF2) a -SO2-NH-SO2R 5 , or (CF2) b -SO3H. R 5 represents a perfluoroalkyl group having 1 to 10 carbon atoms, a represents an integer of 1 to 10, and b represents an integer of 1 to 10.
[0029] The ionomer having the unit structure represented by the formula (1) is A 1 In the case where the ionomer does not have an acid group in the formula (1), for example, the ionomer does not have an acid group, but has a structural unit containing a proton-conducting group such as an acid group. Specific examples of ionomers having high oxygen permeability include ionomers having a unit structure represented by the following formula (2).
[0030] [ka]
[0031] The dispersion solvent disperses the catalyst particles and the ionomer. The dispersion solvent is a polar solvent having a Rohrschneider polarity parameter P' of 5.1 or more, or a mixed solvent containing the polar solvent in a blending ratio of 70% or more. The polar solvent may be at least one selected from the group consisting of water (P'=10.2), dimethyl sulfoxide (P'=7.2), ethylene glycol (P'=6.9), acetonitrile (P'=5.8) and acetone (P'=5.1), or may be at least one of water and ethylene glycol. Examples of solvents having a Rohrschneider polarity parameter of less than 5.1 include ethanol (P'=4.3), n-propanol (P'=4), isopropyl alcohol (P'=3.9), etc. The dispersion solvent may contain a solvent having a Rohrschneider polarity parameter of less than 5.1 in a blending ratio of 30% or less.
[0032] The catalyst ink of the present disclosure is for use in a fuel cell electrode, and more specifically, is used in the catalyst layer of a fuel cell electrode. The catalyst layer of the present disclosure comprises the catalyst particles of the present disclosure. The catalyst layer of the present disclosure may be a cathode catalyst layer, an anode catalyst layer, or both a cathode catalyst layer and an anode catalyst layer.
[0033] [Production of catalyst layer] The catalyst layer of the present disclosure is formed by applying a catalyst ink to a substrate. After applying the catalyst ink to the substrate, the dispersion solvent in the catalyst ink may be removed. The dispersion solvent may be removed by heating and drying the catalyst ink after it has been applied to the substrate.
[0034] The catalyst ink may be obtained by dispersing a raw material mixture containing catalyst particles, a carrier, an ionomer, and a dispersion solvent. The raw material mixture may be dispersed, for example, by a method using an ultrasonic homogenizer, a jet mill, a ball mill such as a bead mill, a high shear, a Filmix, or the like. Dispersion conditions such as dispersion time are not particularly limited and can be set appropriately.
[0035] The substrate may be, for example, polytetrafluoroethylene (PTFE).
[0036] Examples of the coating method include die coating, spin coating, screen printing, doctor blade, squeegee, spray coating, and applicator. The heating speed and heating time of the catalyst ink during coating can be appropriately set depending on the type of dispersion solvent, etc. In addition, the removal speed of the dispersion solvent may be increased by degassing at the same time as heating. The coating thickness of the catalyst layer may be 2.0 to 30 μm.
[0037] The fuel cell may have only one unit cell, or may be a fuel cell stack in which a plurality of unit cells are stacked. In this disclosure, both the single cell and the fuel cell stack may be referred to as a fuel cell. The number of stacked unit cells is not particularly limited, and may be, for example, from 2 to several hundred.
[0038] The single cell comprises at least a membrane electrode gas diffusion layer assembly. The membrane electrode gas diffusion layer assembly has, in this order, an anode gas diffusion layer, an anode catalyst layer, an electrolyte membrane, a cathode catalyst layer, and a cathode gas diffusion layer.
[0039] The cathode (oxidant electrode) includes a cathode catalyst layer and a cathode-side gas diffusion layer. The anode (fuel electrode) includes an anode catalyst layer and an anode-side gas diffusion layer. The cathode and anode are collectively referred to as the electrodes. The cathode catalyst layer and the anode catalyst layer are collectively referred to as catalyst layers.
[0040] The cathode side gas diffusion layer and the anode side gas diffusion layer are collectively referred to as a gas diffusion layer. The gas diffusion layer may be a gas-permeable conductive member or the like. Examples of the conductive member include porous carbon materials such as carbon cloth and carbon paper, and porous metal materials such as metal mesh and foamed metal.
[0041] The electrolyte membrane may be a solid polymer electrolyte membrane. Examples of the solid polymer electrolyte membrane include a fluorine-based electrolyte membrane such as a thin film of perfluorosulfonic acid containing water, and a hydrocarbon-based electrolyte membrane. The electrolyte membrane may be, for example, a Nafion membrane (manufactured by DuPont).
[0042] The single cell may include two separators that sandwich both sides of the membrane electrode gas diffusion layer assembly as necessary. One of the two separators is an anode side separator, and the other is a cathode side separator. In the present disclosure, the anode side separator and the cathode side separator are collectively referred to as separators. The separator may have holes forming manifolds such as supply holes and exhaust holes for passing fluids such as reactant gases and cooling media in the stacking direction of the unit cells. As the cooling medium, for example, a mixed solution of ethylene glycol and water can be used to prevent freezing at low temperatures, and cooling air can also be used. Examples of the supply hole include a fuel gas supply hole, an oxidant gas supply hole, and a coolant supply hole. Examples of the exhaust hole include a fuel gas exhaust hole, an oxidant gas exhaust hole, and a coolant exhaust hole. The separator may have a reactant gas flow path on the surface in contact with the gas diffusion layer, and may have a coolant flow path on the surface opposite to the surface in contact with the gas diffusion layer for maintaining a constant temperature of the fuel cell. The separator may be a gas-impermeable conductive material. The conductive material may be, for example, dense carbon made by compressing carbon to make it gas-impermeable, or a press-formed metal (e.g., iron, aluminum, stainless steel, etc.). The separator may also have a current collecting function.
[0043] In this disclosure, the fuel gas and the oxidant gas are collectively referred to as reactant gases. The reactant gas supplied to the anode is the fuel gas, and the reactant gas supplied to the cathode is the oxidant gas. The fuel gas is a gas that mainly contains hydrogen and may be hydrogen. The oxidant gas is a gas that contains oxygen and may be air or the like.
[0044] The fuel cell stack may have manifolds, such as an inlet manifold to which the supply holes communicate, and an outlet manifold to which the exhaust holes communicate. Examples of the inlet manifold include a fuel gas inlet manifold, an oxidant gas inlet manifold, and a coolant inlet manifold. Examples of the outlet manifold include a fuel gas outlet manifold, an oxidant gas outlet manifold, and a coolant outlet manifold. EXAMPLES
[0045] (Examples 1 to 7, Comparative Examples 1 to 3) A dispersion solvent containing the solvents shown in Table 1 in the blending ratios shown in Table 1 was prepared.
[0046] [Table 1]
[0047] (A) Specific surface area is 40m 2When carbon support particles with a Specific surface area is 40m 2 The catalyst particles (catalytic metal-supported carbon support A) in which catalytic metal particles are supported on carbon support particles having a molecular weight of 1.001 g / g and an ionomer having a unit structure represented by the above formula (2) as an ionomer having high oxygen permeability and proton conductivity were prepared. The density ρ of the ionomer was 1.93 g / cm 3 , number average molecular weight Mn is 39000, EW is 735g / mol, electrical conductivity σ H The oxygen permeability at 80°C and 30% relative humidity is 2.7×10 -14 It was mol / m / sec / Pa. The catalyst particles and ionomer were then dispersed in a dispersion solvent to prepare catalyst inks A for each of Examples 1 to 7 and Comparative Examples 1 to 3. Each catalyst ink A was applied to each substrate to form a catalyst layer A. Two catalyst layers A were prepared, one of which was used as a cathode catalyst layer and the other as an anode catalyst layer, to prepare a fuel cell A equipped with a membrane electrode gas diffusion layer assembly.
[0048] [Rating A] For catalyst ink A, the amount of ionomer adsorption per unit specific surface area of catalytic metal-supported carbon support A in catalyst ink A was measured. The amount of ionomer adsorption per unit specific surface area of catalytic metal-supported carbon support A was measured based on the method described in Patent Document 1. The degree of cracking was also evaluated for catalyst layer A. The amount and size of cracks in the catalyst layer observed under a microscope were visually judged as ○ or ×. Large amounts and sizes of cracks were judged as ×, small amounts and sizes of cracks as △, and no or almost no cracks as ◯. FIG. 1 is an image showing the criteria for judging whether a catalyst layer has cracks, with the image on the left being rated as "x," the image in the middle being rated as "△," and the image on the right being rated as "o." Furthermore, the performance of fuel cell A was evaluated. The performance was judged from the power generation time of the fuel cell and the amount of gas leakage between the anode and cathode in a specified accelerated test. A threshold value of 0.005 MPa or more for the amount of gas leakage between the anode and cathode was set, and the time taken for the threshold value to be reached or exceeded was judged as "X" if it was less than 500 hours, "△" if it was between 500 hours and 1000 hours, and "◯" if it was more than 1000 hours. The results are shown in Table 2.
[0049] [Table 2]
[0050] (B) Specific surface area is 1600m 2 When carbon support particles with a Specific surface area is 1600m 2 Catalyst particles (catalytic metal-supported carbon support B) in which catalytic metal particles are supported on carbon support particles having a molecular weight of 0.1 to 1.0 μg / g, and an ionomer having a unit structure represented by the above formula (2) as an ionomer having high oxygen permeability and proton conductivity were prepared. The catalyst particles and ionomer were then dispersed in a dispersion solvent to prepare catalyst inks B for each of Examples 1 to 7 and Comparative Examples 1 to 3. Each catalyst ink B was applied to each substrate to form a catalyst layer B. Two catalyst layers B were prepared, one of which was used as a cathode catalyst layer and the other as an anode catalyst layer, to prepare a fuel cell B equipped with a membrane electrode gas diffusion layer assembly.
[0051] [Rating B] For catalyst ink B, the amount of ionomer adsorbed per unit specific surface area of catalyst metal-loaded carbon support B in catalyst ink B was measured in the same manner as in evaluation A. In addition, the degree of cracking of the catalyst layer B was evaluated in the same manner as in evaluation A. Furthermore, the performance of fuel cell B was evaluated in the same manner as in evaluation A. The results are shown in Table 3.
[0052] [Table 3]
[0053] As shown in Tables 2 and 3, in the present disclosure, the amount of ionomer adsorbed onto the carrier can be improved by reducing the affinity between the solvent and the ionomer, and cracks that occur in electrodes using ionomers with high oxygen permeability can be suppressed.
Claims
1. A catalyst ink for a fuel cell electrode, comprising: A catalyst particle including a support and a catalytic metal supported on the support; An ionomer having high oxygen permeability and proton conductivity; A dispersion solvent for dispersing the catalyst particles and the ionomer, Catalyst ink characterized in that the dispersion solvent is a polar solvent having a Rohrschneider polarity parameter of 5.1 or more, or a mixed solvent containing the polar solvent in a blending ratio of 70% or more.
2. The catalyst ink according to claim 1 , wherein the ionomer has a five-membered ring in its unit structure.
3. 2. The catalyst ink according to claim 1, wherein the polar solvent is at least one selected from the group consisting of water, dimethylsulfoxide, ethylene glycol, acetonitrile, and acetone.
4. The catalyst ink of claim 1 , wherein the polar solvent is at least one of water and ethylene glycol.
5. The specific surface area of the carrier is 40 to 1600 m 2 2. The catalyst ink of claim 1, wherein the molecular weight of the catalyst ink is 1 / g.
Citation Information
Patent Citations
Electrode for fuel cell, manufacturing method thereof, solid polymer fuel cell, and method for manufacturing catalyst ink
JP2016058396A
Ionomer-coated catalyst and method for manufacturing the same, and catalyst ink
JP2018152333A
Polyelectrolyte
JP2021061220A
Fluoropolymers containing pendant groups with ionic bis(sulfonyl)imide moieties and perfluoroether end groups
JP2023519957A
Catalyst ink for fuel cell electrode, membrane electrode assembly, and fuel cell
JP2013030287A
